2016
DOI: 10.1186/s13045-016-0287-9
|View full text |Cite
|
Sign up to set email alerts
|

Short telomere length and its correlation with gene mutations in myelodysplastic syndrome

Abstract: BackgroundTelomere erosion can lead to genomic instability and cancer progression. It has been suggested that the shortest telomere, not the average telomere length (TL), is critical for cell viability. Some studies have shown shorter TL in myelodysplastic syndrome (MDS) patients but the critically short telomeres, the variability of TL within individual patient has not been evaluated. Thus, we aimed to investigate the TL of MDS patients and assessed the association of TL with recurrent genetic mutations in MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…HRs and 95% CIs for OS and LFS were also extracted from the included studies together with the number of patients which survived every year after diagnosis. If the article provided 19 Wu, 2016 20 Jung, 2016 17 Hwang, 2016 16 Kang, 2015 18 Hong, 2015 15 Kim, 2017 13 Tefferi, 2018 21 Hamilton, 2019 22 Xu, 2017 26 Tefferi, 2017 24 Heuser, 2017 23 Wu, 2013 25 Journal Genes Chromosomes…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRs and 95% CIs for OS and LFS were also extracted from the included studies together with the number of patients which survived every year after diagnosis. If the article provided 19 Wu, 2016 20 Jung, 2016 17 Hwang, 2016 16 Kang, 2015 18 Hong, 2015 15 Kim, 2017 13 Tefferi, 2018 21 Hamilton, 2019 22 Xu, 2017 26 Tefferi, 2017 24 Heuser, 2017 23 Wu, 2013 25 Journal Genes Chromosomes…”
Section: Data Extractionmentioning
confidence: 99%
“…Abnormal karyotypes were encountered significantly more often in patients with than without U2AF1 mutations (49.6% vs. 37.8%, P < 0.05); similarly, patients with abnormal karyotypes were significantly more likely to have U2AF1 mutations (19.3% vs 12.1%, P < 0.05) ( Figure 2). As shown in Figure 3a-d, we analyzed the ORs of OS in MDS patients with U2AF1 mutations in eight studies; 13,[15][16][17][18][19][20][21] summary ORs for OS of 1, 2, 3, and 5 years were 0.76 (95% CI: 0.54-1.09), 0.47 (95% CI: 0.35-0.62, P < 0.001), 0.43 (95% CI: 0.24-0.78, P ¼ 0.006), and 0.37 (95% CI: 0.26-0.51, P < 0.001), respectively. In the case of 3-year OS, high heterogeneity was observed with an I 2 of 64% (P ¼ 0.006).…”
Section: Outcome Of the Meta-analysismentioning
confidence: 99%
“…In this study, we found that a subset of AAH showed significant telomere shortening and expression of AMACR, suggesting a precursor role for AAH lesions in adenocarcinoma evolution. Telomere shortening induces chromosomal instability that can result in tumorigenesis . Because telomere shortening is a progressive process related to cell replication, the discrepancies of relative telomere length among AAH lesions may represent different stages in their development toward malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that telomere attrition along with somatic mutation precede monosomy 7 and the accumulation of short telomeres gives rise to aneuploidy, which may lead to the progression of MDS/AML in patients with severe aplastic anemia . On the other hand, it has also been argued that the regulation of telomere length occurs because of oncogenic mutations already existing in MDS patients …”
Section: Discussionmentioning
confidence: 99%
“…21 On the other hand, it has also been argued that the regulation of telomere length occurs because of oncogenic mutations already existing in MDS patients. 22 Our third aim was to evaluate the survival outcomes of patients who developed MDS/AML. Patients with Fanconi anemia had the worst survival outcome.…”
Section: Discussionmentioning
confidence: 99%